Influence of the capping of biogenic silver nanoparticles on their toxicity and mechanism of action towards Sclerotinia sclerotiorum - Mariana Guilger-Casagrande (Journal of Nanobiotechnology, 2021)
Abstract Background Biogenic nanoparticles possess a capping of biomolecules derived from the organism employed in the synthesis, which contributes to their stability and biological activity. These nanoparticles have been highlighted for the control of phytopathogens, so there is a need to understand their composition, mechanisms of action, and toxicity. This study aimed to investigate the importance of the capping and compare the effects of capped and uncapped biogenic silver nanoparticles synthesized using the filtrate of Trichoderma harzianum against the phytopathogenic fungus Sclerotinia sclerotiorum. Capping removal, investigation of the composition of the capping and physico-chemical characterization of the capped and uncapped nanoparticles were performed. The effects of the nanoparticles on S. sclerotiorum were evaluated in vitro. Cytotoxicity and genotoxicity of the nanoparticles on different cell lines and its effects on nontarget microorganisms were also investigated. Results The capped and uncapped nanoparticles showed spherical morphology, with greater diameter of the uncapped ones. Functional groups of biomolecules, protein bands and the hydrolytic enzymes NAGase, β-1,3-glucanase, chitinase and acid protease from T. harzianum were detected in the capping. The capped nanoparticles showed great inhibitory potential against S. sclerotiorum, while the uncapped nanoparticles were ineffective. There was no difference in cytotoxicity comparing capped and uncapped nanoparticles, however higher genotoxicity of the uncapped nanoparticles was observed towards the cell lines. Regarding the effects on nontarget microorganisms, in the minimal inhibitory concentration assay only the capped nanoparticles inhibited microorganisms of agricultural importance, while in the molecular analysis of the soil microbiota there were major changes in the soils exposed to the uncapped nanoparticles. Conclusions The results suggest that the capping played an important role in controlling nanoparticle size and contributed to the biological activity of the nanoparticles against S. sclerotiorum. This study opens perspectives for investigations concerning the application of these nanoparticles for the control of phytopathogens.